The Influence of Principals’ Transformational Leadership and Teacher Commitment on Learning Quality - Neng Nurhemah; Akhiruddin; Herdi Wisman Jaya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study aims to analyze the influence of principals’ transformational leadership and teacher commitment on learning quality at Yayasan IPTEK Tangerang Selatan. The research employed a quantitative approach with a correlational method. The population consisted of all teachers under the foundation, totaling 83 respondents; therefore, total sampling was applied. Data were collected using a questionnaire and analyzed through the Kolmogorov-Smirnov normality test, multiple linear regression, ANOVA (F-test), partial t-test, and multicollinearity test. The results indicate that all variables were normally distributed, as shown by Asymp. Sig. values greater than 0.05. The ANOVA test produced F = 76.524 with Sig. = 0.000, confirming that transformational leadership and teacher commitment simultaneously have a significant effect on learning quality. Partially, transformational leadership showed a positive and significant effect (B = 0.432; Sig. = 0.000), and teacher commitment also demonstrated a positive and significant effect (B = 0.517; Sig. = 0.000). The R Square value of 0.656 suggests that 65.6% of the variance in learning quality can be explained by the combined influence of transformational leadership and teacher commitment. These findings emphasize that strengthening learning quality requires both effective transformational leadership and strong professional commitment among teachers within the school organization.